2018
DOI: 10.11567/met.34.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Demogeografski razvoj hrvatskog pograničja 2001. – 2011.

Abstract: Rad se bavi demografskim procesima u hrvatskome pograničnom području tijekom posljednjega međupopisnog razdoblja 2001.-2011. Pristup analizi je demogeografski, stoga je naglasak na prostornoj analizi demografskih podataka. Pogranično područje izdvojeno je na temelju jedinica lokalne samouprave (JLS), tj. općina i gradova koji dotiču granicu. Demogeografski pristup izdvojio je tri razine analize: pograničje u cjelini, općine/gradovi koji izlaze na granicu te pogranična naselja, unutar kojih su posebno razmatran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…The study area covers 412.56 km 2 and, according to the 2011 census, the area has 35,799 residents. The overall population density in 2011 was 86.8 per km 2 , exceeding the Croatian national average of 75.7 per km 2 (Pokos, 2017;Zupanc, 2018) najveće urbano središte prostora, bilježi konstantan rast stanovništva, dok ostala naselja uglavnom bilježe blagi pad. Iako je situacija osjetno bolja nego u ostatku Hrvatske, najnoviji trendovi nisu najpovoljniji.…”
Section: Study Areamentioning
confidence: 90%
See 1 more Smart Citation
“…The study area covers 412.56 km 2 and, according to the 2011 census, the area has 35,799 residents. The overall population density in 2011 was 86.8 per km 2 , exceeding the Croatian national average of 75.7 per km 2 (Pokos, 2017;Zupanc, 2018) najveće urbano središte prostora, bilježi konstantan rast stanovništva, dok ostala naselja uglavnom bilježe blagi pad. Iako je situacija osjetno bolja nego u ostatku Hrvatske, najnoviji trendovi nisu najpovoljniji.…”
Section: Study Areamentioning
confidence: 90%
“…Površina proučavanoga prostora iznosi 412,56 km 2 , a prema popisu stanovništva iz 2011. godine područje broji 35 799 stanovnika. Opća gustoća naseljenosti iznosi 86,8 stan./km 2 , što premašuje hrvatski prosjek od 75,7 stan./km 2 iz 2011. godine (Pokos, 2017;Zupanc, 2018). Grad Metković, kao There have been no studies regarding changes in land use and land cover in the Lower Neretva Region to date.…”
Section: Područje Istraživanjaunclassified
“…Delimitation methods for borderlands are often based on administrative criteria, encompassing the municipalities or regions along state borders. This principle is widely used, particularly in geographic research (Zupanc 2018;Anđelković-Stoilković 2019), because of the availability of statistical data, but there are also range of other criteria (Jeřábek et al 2004;Bufon 2007;Nejašmić 2008;Máliková et al 2015).…”
Section: Definition Of Borderlands Of Bosnia and Herzegovinamentioning
confidence: 99%
“…Borderlands research in Southeast Europe (e.g., in Serbia and Croatia) has applied a range of methodological approaches to confirm the hypothesis of border regions as economically, socially and demographically marginalized parts of the national territory (Popović and Radeljak 2011;Zorko 2012;Pejnović and Kordej-De Villa 2015;Vukmirović et al 2016). In comparing the socio-economic indicators of border regions with the national average and examining the standard of living in these areas (Máliková et al 2015;Đerčan et al 2016), determining the incidence of demographic issues (Zupanc 2018;Anđelković-Stoilković 2019) and analyzing borderlands in the context of national security (Vukmirović et al 2016), multiple authors have concluded that border regions are observed through the paradigm of spatial polarization due to the disparity in the levels of development between the center and periphery.…”
Section: Introductionmentioning
confidence: 99%